An 8-Hydroxy-Quinoline Derivative Protects Against Lipopolysaccharide-Induced Lethality in Endotoxemia by Inhibiting HMGB1-Mediated Caspase-11 Signaling - Wang, Xiangyu; Shi, Jian; Li, Zhaozheng; Li, Ling; Zhang, Rui; Bai, Yang; Li, Junmei; Liang, Fang; Tang, Yiting (Frontiers in Pharmacology, 2021)
Sepsis, an inflammatory syndrome secondary to infection, is the leading cause of in-hospital lethality. It is evidenced that LPS, the major pathological component of Gram-negative bacteria membrane, predominantly contributes to the pathogenesis of sepsis. Cytoplasmic lipopolysaccharide (LPS) can be sensed by non-canonical inflammasome and triggers the oligomerization of caspase-11, resulting in pyroptosis and lethal immune responses in sepsis. A previous study shows that hepatocyte-released high mobility group box 1 (HMGB1) mediates caspase-11 dependent lethality in sepsis by delivering extracellular LPS into the cytosol. Here, we established a phenotypic screening system using recombinant HMGB1 plus LPS in mouse peritoneal macrophages, identifying a novel 8-hydroxyquinoline derivative named 7-[phenyl(pyridin-2-ylamino) methyl] quinolin-8-ol (8-ol, NSC84094) that can specifically inhibit HMGB1-mediated caspase-11 signaling. 8-ol targets directly to HMGB1 and changes the secondary conformation, consequently disrupts the interaction between LPS and HMGB1 and inhibits the HMGB1-mediated delivery of LPS into the cytosol. Intervention of 8-ol significantly reduced the release of IL-1α and IL-1β，and protected against caspase-11-mediated organ injury and lethality in endotoxemic mice. Thus, this study clearly suggests that the HMGB1-caspase-11 pathway is a potential drug target in the lethal immune disorders and might open a new avenue in the treatment of sepsis.